Gait adaptability training for individuals with non-progressive neurological conditions: a scoping review of intervention characteristics and outcome measures. - Cesca, Nicole; Heffernan, Matthew G; Winokur, Sydney; Chan, Katherine; Pujol-Fuentes, Clara; Musselman, Kristin E (PTJ: Physical Therapy & Rehabilitation Journal, 2026)
Importance Gait adaptability is essential for safe walking. Impairments after non-progressive neurological conditions contribute to walking limitations and fall risk. Advances in virtual/augmented reality-based treadmills/walkways have increased interest in gait adaptability assessment and training, making a review timely. Objective The objectives were as follows: (1) Explore the characteristics and outcomes of physical interventions used to improve gait adaptability for individuals with non-progressive neurological conditions; and (2) Identify the outcome measures and tasks used to track changes with interventions incorporating gait adaptability training. Data Sources A comprehensive search was conducted in 6 databases: CINAHL Complete, Embase, Emcare Nursing, Medline ALL, PEDro, and Web of Science Core Collection, from inception to September 8, 2025. Study Selection Studies that involved adults with non-progressive neurological conditions, incorporated walking with environmental/task changes, targeted gait adaptability, and included >2 training sessions were included. Data Extraction and Synthesis Study/participant characteristics, interventions, and outcomes were extracted. Methodological quality was assessed using the Modified Downs and Black checklist. Interventions were categorized into 6 groups, and their alignment with 9 gait adaptability domains was evaluated. Outcome measures were identified and classified based on relevance to gait adaptability. Results Twenty-nine studies (881 participants: 743 stroke, 132 spinal cord injury, 6 acquired brain injury) were included. The most common interventions were skilled overground/community walking and treadmill training with virtual/augmented reality. Obstacle negotiation was the most frequently targeted gait adaptability domain. Interventions that incorporated gait adaptability training led to improvements in walking outcomes such as speed and endurance. The most common outcome measures—10-Meter Walk Test, Timed Up and Go, and 6-Minute Walk Test—do not directly assess gait adaptability. Conclusions and Relevance Interventions that incorporated gait adaptability training included a broad range of overground and treadmill training approaches, and improved walking ability. Future trials should include measures that directly assess multiple domains of gait adaptability.